POLITIK HUKUM PENENTUAN TINGKAT PENDIDIKAN SEBAGAI SYARAT MENJADI ANGGOTA DEWAN PERWAKILAN RAKYAT DI INDONESIA DALAM PERSPEKTIF RANCANGAN UNDANG-UNDANG TENTANG PEMILIHAN UMUM - Muhammad Rafi Akbar; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The DPR has a central role in the constitutional system in Indonesia.Given the enormous role of the DPR in the state administration system inIndonesia, the minimum education requirements set forth in Article 240paragraph (1) letter e of Law No. 7 of 2017 concerning General Elections mustbe renewed/reformulated. Because these regulations are felt to have weaknesses,whereby an institution that has the function and authority to make and issue alegal product and determine policies may nominate themselves as a candidate formembers of the DPR with at least a high school educational background orequivalent. The aim of the reformulation of the system for nominating members ofthe DPR is so that the legal and policy products that will be issued by membersof the DPR can be better and more beneficial to the general public.This research is a normative legal research. This is based on libraryresearch which takes excerpts from reading books, or supporting books that havesomething to do with the problem to be studied. This study uses secondary datasources consisting of primary, secondary and tertiary legal materials. This studyalso used qualitative data analysis and produced descriptive data.From the results of this study it is explained that there is a need toincrease the standardization of the minimum educational requirements to becomea candidate for DPR member. The ideal concept offered by researchers is toincrease or reformulate the minimum educational requirements for candidatesfor DPR members, from a minimum high school diploma to a minimum of abachelor's degree (S1). Some of the considerations that form the basis forforming regulations are: First, on the Aspect of Justice, because to guaranteecompetence, capability and also guarantee the placement of members of the DPRin accordance with their respective portions based on their educationalbackground, so that they are more professional in carrying out their duties andfunctions. Second, on the Certainty Aspect, the minimum educationalqualification requirements for candidates for DPR members are stipulatedthrough clear legal instruments that will provide legal certainty. Third, on theUsefulness Aspect, so that in every contribution a DPR member makes incarrying out his authority, duties and functions it will be better.Keywords: Reformulation-Requirements-Education-DPR